Sexual sadism and criminal versatility: does sexual sadism spillover into nonsexual crimes?. Issue 1 (9th January 2017) - DeLisi, Matt; Drury, Alan; Elbert, Michael; Tahja, Katherine; Caropreso, Daniel; Heinrichs, Timothy
Abstract : Purpose: Sexual sadism is a well-known risk factor for severe forms of sexual violence including sexual homicide and serial sexual homicide. The research is decidedly mixed about the association between sexual sadism and other, nonsexual forms of criminal conduct. The paper aims to discuss these issues. Design/methodology/approach: Drawing on data from a census of 225 federal sex offenders from a jurisdiction in the Midwestern USA, the current study examined whether sexual sadism had a spillover effect into nonsexual crimes using correlation, ANOVA, and negative binomial regression models. Findings: Sexual sadism was strongly associated with diverse forms of nonsexual criminal behavior, and sexual sadists had more extensive and versatile criminal careers than sex offenders without a formal diagnosis. Practical implications: Practitioners should be aware of sexual sadism as a criminogenic risk factor. Sexual sadism is associated with sexual deviance and sexual violence. Sexual sadism also has spillover effects where it is associated with nonsexual offending. Originality/value: Sexual sadism can be a useful risk factor for other forms of crime and recidivism and has broad application in applied correctional and research settings.